Case report: Primary immunodeficiency due to a novel mutation in CARMIL2 and its response to combined immunomodulatory therapy - Zhu, Yu; Ye, Lili; Huang, Hua; Xu, Xuemei; Liu, Yu; Wang, Jian; Jin, Yanliang (Frontiers in Pediatrics, 2023)
CARMIL2 is necessary for invadopodia formation, cell polarity, lamellipo¬dial assembly, membrane ruffling, acropinocytosis, as well as collective cell migration. CARMIL2 deficiency is a rare autosomal recessive disease, which is characterized by the dysfunction of naïve T cell activation, proliferation, differentiation as well as effector function and insufficient gain of T-cell memory. In this paper, we report a 9-year-old female patient with a novel pathogenic variant in CARMIL2 (c.2063C>G:p.Thr688Arg), who presented with various symptoms of PID including recurrent upper and lower respiratory infections, perioral and perineum papules, reddish impetiginized atopic dermatitis, oral ulcers, painful urination and vaginitis, otitis media as well as failure to thrive. Besides, the missense mutation led to the insufficient CARMIL2 protein expression, reduced absolute T cell and NK cell counts and the marked skewing to the naïve form indicated defective maturation of T cells and B cells. After the multi-targeted treatment of corticosteroid, hydroxychloroquine, mycophenolate mofetil and thymosin for one year, the patient presented significant regression of rashes.CD4+T cells, CD8+ T cells and NK cells did exhibit significant rescued.